Analysis of the Role of the Social Service in the Guidance of Street Children (Case Study at the Office of the Social Service for Social Rehabilitation in Medan City) - Annisa Annisa (Penerbit Jurnal Indonesia, 2022)
Sosial Service is an element of the implementation of government affairs which is the authority of the region. The Sosial Service who is under and responsible to the regent through the regional secretary. The Sosial Service has the task of assisting the regent in carrying out government affairs which are the authority of the region and the assistance tasks given to the region in the sosial sector. The office of social affairs and public services in the fields of social rehabilitation and social protection guarantees, social empowerment and handling the poor. With the number of abandoned street children in the city of medan, the role of the social service is very much needed in the context of child rehabilitation for street children. This study aims to determine how the role of the social service in fostering street children in the city of medan. This study uses describe and explain the role of the social service in fostering street children in the city of Medan.